Collaborating to solve food insecurity in Rural Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Onai R. S. Mtengwa of the University of Venda, South Africa talks about the use of under utilized crops to ensure food security in rural communities of Africa. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/... http://www.fara-africa.org/scienceweek/